Partial Replacement of Alum by Using Natural Coagulant Aid to Remove Turbidity from Institutional Wastewater - Kumar, Vicky (International Journal of Integrated Engineering, 2020)
The quality of water is superior for the stability of the ecosystem. Institutional wastewater contains pollutants and exceed the level of contaminants beyond standards. Applications of natural coagulants are widely in practice due to abundant source, low price, environment-friendly and rapid biodegradable as compared to inorganic based coagulants. This study traces the potential removal of pollutants from institutional wastewater by coagulation-flocculation processes. Alum as primary coagulant and cassava peel starch as natural coagulant aid was used for removal of pollutants. The use of alum dose in wastewater treatment plant has harmful effects on human health and water drainage system, on the one hand and on the other hand, a process that alum coagulant dose used in wastewater treatment plant with a high processing cost. In this study, the use of cassava peels starch (CPS) (as a natural coagulant) instead of alum dose to treat wastewater to remove turbidity from institutional wastewater. The study samples were taken from the Tun Fatimah-UTHM. Experimental runs were carried out for three hours per run over weekend period with turbidities ranging from 20 to 400 NTU. Proven results of the study that by using natural coagulant CPS (which is a naturally contains potentials) instead of alum does not carry any impact on human health and has a high efficiency up to 81% in the removal of turbidity from institutional wastewater at pH 8. The turbidity ranges during most of the test runs satisfied the WHO and water quality standards (A & B) for potable water supplies.